Chitosan-silica Sulfate Nano Hybrid: An Efficient Biopolymer Based-heterogeneous Nano Catalyst for Solvent-free Synthesis of 3,4-Dihydropyrimidine-2(1H)-one/thiones - Somayeh Behrouz (Acta Chimica Slovenica, 2021)
A green and highly efficient approach for the synthesis of 3,4-dihydropyrimidine-2(1H)-one/thione derivatives is described. In this approach, the three-component Biginelli reaction between (thio)urea, methyl acetoacetate and aldehydes under solvent-free condition in the presence of chitosan-silica sulfate nano hybrid (CSSNH) as a green and heterogeneous nano catalyst affords the corresponding products in good to excellent yields and in short reaction times. CSSNH is a cheap, eco-friendly, and non-toxic nano catalyst that could be easily prepared, handled, and reused for many reaction runs without significant loss of its activity.